Strategi Pengelolaan BUMDes Amarta Dalam Penguatan Ekonomi Desa Pandowoharjo - Kurata Rahma Aulia; Nur Ameliah Ispi; Winda Irmayani (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2023)
Amarta BUMDes located in Pandowoharjo Village, Sleman Regency. BUMDes Amarta Pandowoharjo Village was established on June 6 2016 and stipulated in Pandowoharjo Village Regulation Number 04 of 2016 concerning the Formation and Management of BUMDes. BUMDes Amarta has five business units and has collaborated with various partners including Bank BRI, Sampoerna, Indonesian Swimming Association and jeJamuran. The method used in this research is descriptive qualitative. Data collection techniques were carried out through participating observations. The results of the study show that the strategy used by BUMDes is able to strengthen the economy of Pandowoharjo Village by increasing the village's original income with a profit sharing system between the manager and the village, BUMDes provides 35% of the profits derived from several business results of the Amarta BUMDes unit for PADes.